2021
DOI: 10.4103/jfmpc.jfmpc_2090_20
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on the microbial spectrum and antibiogram of uropathogens in children in a secondary care hospital in Rural Vellore, South India

Abstract: Background: Urinary tract infection (UTI) is common among children. Empiric antibiotics have to be started as early as possible or it may lead to an irreversible renal parenchymal damage and renal scarring in children. The objectives were to determine the prevalence and microbial profile of paediatric UTI and to determine the antimicrobial susceptibility pattern. Methodology: This is a retrospective study which looked at urine cultures of children below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 16 publications
4
12
3
Order By: Relevance
“…Furthermore, our finding is in accordance with that of other studies as we isolated 83.4% of gram-negative bacteria as pathogens. E. coli was the most common isolate responsible for 54.4% of infectious cases, and this finding is in accordance with that of several studies [ 1 - 3 , 10 , 14 ]. Enterococcus faecium was the second most common isolate in our study.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Furthermore, our finding is in accordance with that of other studies as we isolated 83.4% of gram-negative bacteria as pathogens. E. coli was the most common isolate responsible for 54.4% of infectious cases, and this finding is in accordance with that of several studies [ 1 - 3 , 10 , 14 ]. Enterococcus faecium was the second most common isolate in our study.…”
Section: Discussionsupporting
confidence: 92%
“…In 76% of cases, pyuria was observed (p < 0.0001), and this result is in contrast to that of the study by Tryphena et al that revealed that pyuria was only observed in 22.5% of cases [ 1 ]. This microscopic finding may act as a guiding tool to start empirical therapy based on the local antibiogram, which needs to be changed after obtaining the urine culture and antimicrobial susceptibility report of patients.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations